2D 7Li Ultrafast CT-COSY: a new tool for the rapid measurement of tiny homonuclear lithium scalar couplings. Issue 1 (5th December 2016) - Hamdoun, G.; Gouilleux, B.; Sebban, M.; Barozzino-Consiglio, G.; Harrison-Marchand, A.; Giraudeau, P.; Maddaluno, J.; Oulyadi, H.
Abstract : We report on the first examples of 7 Li Ultrafast (UF) CT-COSY spectra from lithiated samples and on the usefulness of these experiments for the quantitative estimation of the 2 J 7 Li– 7 Li in a much shorter time. Abstract : The measurement of small homonuclear 2 J 7 Li– 7 Li scalar couplings relying on constant time (CT) COSY NMR suffers from strong time limitations. We describe the first Ultrafast CT COSY experiment on lithium 7, which provides a considerable acceleration in the study of the aggregation state and dynamics of n -BuLi/MeLi complexes.